5-Aminolevulinic Acid Improves Morphogenesis and Na+ Subcellular Distribution in the Apical Cells of Cucumis sativus L. Under Salinity Stress - Wu, Yue; Liu, Na; Hu, Linli; Liao, Weibiao; Tang, Zhongqi; Xiao, Xuemei; Lyu, Jian; Xie, Jianming; Calderón-Urrea, Alejandro; Yu, Jihua (Frontiers in Plant Science, 2021)
Soil salinity causes damage to plants and a reduction in output. A natural plant growth regulator, 5-aminolevulinic acid (ALA), has been shown to promote plant growth under abiotic stress conditions. In the present study, we assessed the effects of exogenously applied ALA (25 mg L−1) on the root architecture and Na+ distribution of cucumber (Cucumis sativus L.) seedlings under moderate NaCl stress (50 mmol L−1). The results showed that exogenous ALA improved root length, root volume, root surface area, and cell activity in the root tips, which were inhibited under salt stress. In addition, although salinity stress increased the subcellular Na+ contents, such as those of the cell wall, nucleus, plastid, and mitochondria, ALA treatment reduced these Na+ contents, except the soluble fraction. Molecular biological analysis revealed that ALA application upregulated both the SOS1 and HA3 transcriptional and translational levels, which suggested that the excretion of Na+ into the cytoplasm cloud was promoted by exogenous ALA. Meanwhile, exogenously applied ALA also upregulated the gene and protein expression of NHX1 and VHA-A under salinity stress, which suggested that the compartmentalization of Na+ to the vacuole was enhanced. Overall, exogenous ALA mitigated the damage caused by NaCl in cucumber by enhancing Na+ redistribution and increasing the cytoactivity of root cells.